(11x-6)+(7x+5)+55=180

Simple and best practice solution for (11x-6)+(7x+5)+55=180 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (11x-6)+(7x+5)+55=180 equation:


Simplifying
(11x + -6) + (7x + 5) + 55 = 180

Reorder the terms:
(-6 + 11x) + (7x + 5) + 55 = 180

Remove parenthesis around (-6 + 11x)
-6 + 11x + (7x + 5) + 55 = 180

Reorder the terms:
-6 + 11x + (5 + 7x) + 55 = 180

Remove parenthesis around (5 + 7x)
-6 + 11x + 5 + 7x + 55 = 180

Reorder the terms:
-6 + 5 + 55 + 11x + 7x = 180

Combine like terms: -6 + 5 = -1
-1 + 55 + 11x + 7x = 180

Combine like terms: -1 + 55 = 54
54 + 11x + 7x = 180

Combine like terms: 11x + 7x = 18x
54 + 18x = 180

Solving
54 + 18x = 180

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-54' to each side of the equation.
54 + -54 + 18x = 180 + -54

Combine like terms: 54 + -54 = 0
0 + 18x = 180 + -54
18x = 180 + -54

Combine like terms: 180 + -54 = 126
18x = 126

Divide each side by '18'.
x = 7

Simplifying
x = 7

See similar equations:

| 2(3x+1)+6(x-2)= | | 0.4(7c+5)=3.1c-2.2 | | (65+59)+9x+2=180 | | 11x+17=180 | | 300-5x=-150 | | 24x+2=50 | | 4-2/3x=-6 | | 27x-5=130 | | 3x^2+2a-90=0 | | -4-9x=41 | | B=900(1+0.1)6 | | 4(5m-3m)-9=3m-4 | | 4x-31/3=182/3 | | 5t-(3t+14)=2t-14 | | 5x^4-3x^2-1=0 | | 76=2x+16 | | x+2n=15n+23 | | 3a+13=9a | | 13-9x=133-37x | | x+2n=5n+23 | | 3x+(2/5)=4x+(4/5) | | (8x+12)=((5x-5)2) | | 6x-7=79-2x | | 9+4x=18x | | 9y-10=5y-54 | | 6x^4-12x^2= | | (3-4)+4*3*-3= | | 72x^2+56x/9x-7 | | 7(2x-8)-6=14x-62 | | 4(m-2)-7+2m=6(m+5) | | (8x+12)=(5x-5) | | 3z+7=35 |

Equations solver categories